Pengaruh Status Hidrasi dan Desaturasi yang Diinduksi Latihan Terhadap Performa Fisik Atlet Klub Bulu Tangkis - Ach Farhan Nur Hidayat; Jajat Darajat Kusumah Negara; Agus Gumilar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the influence of hydration status (HS) and the exercise-induced muscle oxygen desaturation ratio (SmO2 Ratio) on physical performance, represented by VO2Max, in adolescent badminton club athletes. Method: A quantitative correlational approach with multiple linear regression and path analysis was used. Ten adolescent athletes (aged 12–15 years) from PB. Mutiara Cardinal Bandung participated as research subjects, selected through purposive sampling. Hydration status was measured post-exercise using a Tanita Body Composition Analyzer (Bioelectrical Impedance Analysis/BIA), while muscle oxygen desaturation was monitored in real time using a Moxy Monitor (Near-Infrared Spectroscopy/NIRS) during a standardized Beep Test. Data were analyzed using correlation, regression, and path analysis. Results: Hydration status showed no significant relationship with either the SmO2 Ratio (r = -0.302, p = 0.396) or VO2Max (r = -0.240, p = 0.505). In contrast, the SmO2 Ratio showed a very strong and significant correlation with VO2Max (r = 0.859, p = 0.001), explaining 73.8% of its variance. Path analysis showed that hydration status influenced VO2Max mainly through the SmO2 Ratio. Muscle oxygen utilization efficiency, as measured by the SmO2 Ratio, is the dominant physiological determinant of aerobic performance in adolescent badminton athletes, surpassing the contribution of hydration status when athletes maintain normal hydration levels. These findings support the integration of NIRS-based monitoring into badminton training practice. Keywords: Badminton, Muscle Oxygen Desaturation, Athletic Performance, Hydration Status, VO2max